Penal subversions: When is a punishment not punishment, who decides and on what grounds? - Zedner, L (SAGE Publications, 2016)
Current criminological interest in the boundaries of penality has done much to shed light on the definition and meaning of punishment. Even the central case of punishment, its aims and purposes are contested, so it should not surprise that the boundaries are also disputed. As states seek to evade the criminal process and its protections by resort to civil and administrative measures, the line between formal and informal criminal penalties blurs. In Europe, the courts have sought to reassert the protections of the criminal process by looking behind the labels to insist on substance over form in deciding what is a punishment. In so doing, they have re-affirmed the boundaries of penality as a vital means of providing protection against arbitrary government. Examining these turf wars reveals a constitutional struggle over the very authority of the state to punish.